Acute Compartment Syndrome and Intra-Abdominal Hypertension, Decompression, Current Pharmacotherapy, and Stable Gastric Pentadecapeptide BPC 157 Solution - Predrag Sikiric; Sven Seiwerth; Anita Skrtic; Mario Staresinic; Sanja Strbe; Antonia Vuksic; Suncana Sikiric; Dinko Bekic; Toni Penovic; Dominik Drazenovic; Tomislav Becejac; Marijan Tepes; et al. (Pharmaceuticals)
In this study, pharmacotherapies of abdominal compartment syndrome (ACS) and intra-abdominal hypertension (IAH) in animal studies were reviewed from the perspective of ACS/IAH as failed cytoprotection issues, as non-specific injuries, and from the point of view of the cytoprotection concept as resolution. Therefore, this review challenges the unresolved theoretical and practical issues of severe multiorgan failure, acknowledged significance in clinics, and resolving outcomes (i.e., open abdomen). Generally, the reported agents not aligned with cytoprotection align with current pharmacotherapy limitations and have (non-)confirmed effectiveness, mostly in only one organ, mild/moderate IAH, prophylactic application, and provide only a tentative resolution. Contrarily, stable gastric pentadecapeptide BPC 157 therapy, as a novel and relevant cytoprotective mediator having pleiotropic beneficial effects, simultaneously resolves many targets, resolving established disturbances, specifically compression/ischemia (grade III and grade IV), and decompression/advanced reperfusion. BPC 157 therapy rapidly activates collateral bypassing pathways, and, in ACS and IAH, and later, in reperfusion, there is a “bypassing key” (i.e., azygos vein direct blood flow delivery). This serves to counteract multiorgan and vessel failure, including lesions and hemorrhages in the brain, heart, lung, liver, kidney and gastrointestinal tract, thrombosis, peripherally and centrally, intracranial (superior sagittal sinus), portal and caval hypertension and aortal hypotension, occlusion/occlusion-like syndrome, advanced Virchow triad circumstances, and free radical formation acting as a membrane stabilizer and free radical scavenger. Likewise, not only in ACS/IAH resolving, but also in other occlusion/occlusion-like syndromes, this “bypassing key” could be an effect of the essential endothelial cytoprotective capacity of BPC 157 and a particular modulatory effect on the NO-system, and a rescuing impact on vasomotor tone.